The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Anais Do XXIV Workshop De Informática Na Escola (WIE 2018) 2018
DOI: 10.5753/cbie.wie.2018.509
|View full text |Cite
|
Sign up to set email alerts
|

O Pensamento Computacional em Atividades de Ensino mediadas pelo Professor do Ensino Fundamental I: Um Estudo de Caso

Abstract: Este trabalho apresenta um estudo de caso sobre práticas educativas voltadas a desenvolver o Pensamento Computacional em crianças. Essas atividades foram construídas e mediadas por docentes que atuam no Ensino Fundamental I de escolas públicas do interior do estado de . Com a aplicação de uma formação continuada para os professores participantes, foram coletados dados qualitativos e conduzida uma análise por meio da Teoria Fundamentada. Os resultados indicam três diferentes formatos de atividades que podem est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…On the other hand, the barrier that the use of technologies still represents for many teachers also appeared in the responses: 79% of the 40 mathematics teachers interviewed by Barros et al [6] declared that in order to use CT concepts in their teaching, they would need the help of an Informatics teacher; and all 13 teachers interviewed by Silva et al [30] cited the lack of computer labs as an obstacle to conduct CT activities. Like Martinelli et al [24], Silva et al [30] also identified the need for more CT courses for teachers.…”
Section: Table 1: Publications On Computational Thinking and Teacher mentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the barrier that the use of technologies still represents for many teachers also appeared in the responses: 79% of the 40 mathematics teachers interviewed by Barros et al [6] declared that in order to use CT concepts in their teaching, they would need the help of an Informatics teacher; and all 13 teachers interviewed by Silva et al [30] cited the lack of computer labs as an obstacle to conduct CT activities. Like Martinelli et al [24], Silva et al [30] also identified the need for more CT courses for teachers.…”
Section: Table 1: Publications On Computational Thinking and Teacher mentioning
confidence: 99%
“…From the 13 papers retrieved in our manual search on CT and teacher development, eight present research with schoolteachers [3,6,10,22,24,25,30,32], and five developed research in higher education [2,13,14,15,19 schoolteachers Souza et al [32] 2016 WAlgProg Costa et al [10] 2017 WAlgProg Leite et al [22] 2017 WAlgProg Silva et al [30] 2017 WIE Martinelli et al [24] 2018 WIE Martinelli and Sakata [25] 2018 WIE Barros et al [6] 2018 SBIE…”
Section: Figure 1: Number Of Publications With "Computational Thinkinmentioning
confidence: 99%
See 2 more Smart Citations
“…A análise da experiência consiste em compreender se o fato de participar da oficina mudou a percepção quanto à profissão da Computação e o quanto dos conceitos de Banco de Dados foram realmente aprendidos. Martinelli et al (2018) apresentam um estudo de caso realizado com docentes do Ensino Fundamental I, com o intuito de capacitá-los a ensinar o Pensamento Computacional aos seus alunos. Foram utilizados diversos artifícios para a criação de atividades que poderiam ser aplicadas nas escolas, destacando tanto as atividades desplugadas quanto as plugadas.…”
Section: Introductionunclassified